Археологические раскопки в Керчи около церкви Иоанна Предтечи - Макарова, Т.И. (Материалы по археологии, истории и этнографии Таврии, 1998)
Excavations in Kerch in former Rynochnaya (Market) Square took place during 6 field seasons: 1963-1964, 1970-1971, 1976 and 1980. A series of 5-meter continuous layers with the remnants of building works was revealed as a result of them. The earliest period is represented by the remains of a Bosporos mint and a buried treasure with coins of the 3d century A.D. A building with a marble floor connected with a basilica complex of Justinian's period and cisterns for salting fish of the 6th - 7th centuries were left from the second period. These fundamental buildings were recovered by the building of Khazar period of the 8th - 9th centuries: a fortress wall of the citadel is traced for 15,3 m. Its destruction is dated back to the 9th century. On the surveyed surface at the depth of 2,1 m from the contemporary one a town block was discovered; it consisted of 5 houses and 2 streets paved with shell rock and broken packing dishes. This Korchev block is dated back to the 10th - 12th centuries and one of the streets leads to the northern entrance to John the Baptist Church. More than 50 stone boxes with burials of the 10th - 14th centuries were excavated near its walls, that testifies for simultaneous building of Korchev block and the church.